O sangue, o direito e a convivência no jogo das filiações - Silva, Júlio César Rocha da (2018)
The present thesis examined the family ways of life and descent after changes in the demographic behaviors in Brazil. The dominant family model composed of a couple and their children coexists today with an increase in diversified family arrangements. Because of these transformations, the family sociology has turned to the plurality of norms that constitute the families, these having in mind their relevance in many discussions in the field of Social Sciences. Understanding that the alliance is not the only way to establish a descent, it is proposed to explain how blood, law and coexistence are articulated in descent institution. Hence, the discussions that permeate the work sessions broached families, descents and their meanings in the current theoretical, legal and current social framework. The basic idea of this work is that, depending on family dynamics, other adults appear to contribute or even care for children / young people and, in these situations, there is the possibility of multi-parenting happens, overlapping the feelings of parenthood. The methods used were the analysis of quantitative data, interviews with sons who experienced multiple parenting and the investigation of paternity / maternity cases from the Sergipe Court of Justice (TJ / SE). The notions of descent, capable of dissociating reproduction and descent, revealed that blood has the force of law, coexistence creates moral duties, and the use of terminology of kinship differs from feelings.